Single‐cell sequencing defines genetic heterogeneity in pancreatic cancer precursor lesions. Issue 3 (16th January 2019) - Kuboki, Yuko; Fischer, Catherine G; Beleva Guthrie, Violeta; Huang, Wenjie; Yu, Jun; Chianchiano, Peter; Hosoda, Waki; Zhang, Hao; Zheng, Lily; Shao, Xiaoshan; Thompson, Elizabeth D; Waters, Kevin; et al.
Abstract: Intraductal papillary mucinous neoplasms (IPMNs) are precursors to pancreatic cancer; however, little is known about genetic heterogeneity in these lesions. The objective of this study was to characterize genetic heterogeneity in IPMNs at the single‐cell level. We isolated single cells from fresh tissue from ten IPMNs, followed by whole genome amplification and targeted next‐generation sequencing of pancreatic driver genes. We then determined single‐cell genotypes using a novel multi‐sample mutation calling algorithm. Our analyses revealed that different mutations in the same driver gene frequently occur in the same IPMN. Two IPMNs had multiple mutations in the initiating driver gene KRAS that occurred in unique tumor clones, suggesting the possibility of polyclonal origin or an unidentified initiating event preceding this critical mutation. Multiple mutations in later‐occurring driver genes were also common and were frequently localized to unique tumor clones, raising the possibility of convergent evolution of these genetic events in pancreatic tumorigenesis. Single‐cell sequencing of IPMNs demonstrated genetic heterogeneity with respect to early and late occurring driver gene mutations, suggesting a more complex pattern of tumor evolution than previously appreciated in these lesions. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.